"Automatic assumption of your gender, sexuality and sexual practices is also discrimination": Exploring sexual healthcare experiences and recommendations among sexually and gender diverse persons in Arctic Canada. (15th April 2019) - Logie, Carmen H.; Lys, Candice L.; Dias, Lisa; Schott, Nicole; Zouboules, Makenzie R.; MacNeill, Nancy; Mackay, Kayley
Abstract: Sexual and mental health disparities are reported in Arctic Canada as in other Arctic regions that experience shared challenges of insufficient healthcare resources, limited transportation, and a scarcity of healthcare research. Lesbian, gay, bisexual, transgender, and queer persons (LGBTQ+) report sexual and mental health disparities in comparison with their heterosexual and cisgender counterparts, and these disparities may be exacerbated in rural versus urban settings. Yet limited research has explored sexual healthcare experiences among LGBTQ+ persons in the Arctic who are at the juncture of Arctic and LGBTQ+ health disparities. We conducted a qualitative study from May 2015 to October 2015 with LGBTQ+ persons in the Northwest Territories, Canada that involved in‐depth individual interviews with LGBTQ+ youth ( n = 16), LGBTQ+ adults ( n = 21), and key informants (e.g. coaches, teachers, nurses, social workers, and healthcare providers) ( n = 14). We conducted thematic analysis, a theoretically flexible approach that integrates deductive and inductive approaches, to identify and map themes in the data. Findings reveal geographical, social, and healthcare factors converge to shape healthcare access. Specifically, the interplay between heterosexism and cisnormativity, intersectional forms of stigma, and place limited LGBTQ+ persons' sexual healthcare access and produced negative experiences in sexual healthcare. Limited healthcare facilities in small communities resulted in confidentiality concerns. Heteronormativity and cisnormativity constrained the ability to access appropriate sexual healthcare. LGBTQ+ persons experienced LGBTQ+, HIV, and sexually transmitted infections stigma in healthcare. Participants also discussed healthcare provider recommendations to better serve LGBTQ+ persons: non‐judgment, knowledge of LGBTQ+ health issues, and gender inclusivity. Findings can inform multi‐level strategies to reduce intersecting stigma in communities and healthcare, transform healthcare education, and build LGBTQ+ persons' healthcare navigation skills.